Experimental study exploring the factors that promote rib fragility in the elderly - Liebsch, Christian (Sci Rep, 2021)
Rib fractures represent a common injury type due to blunt chest trauma, affecting hospital stay and mortality especially in elderly patients. Factors promoting rib fragility, however, are little investigated. The purpose of this in vitro study was to explore potential determinants of human rib fragility in the elderly. 89 ribs from 13 human donors (55–99 years) were loaded in antero-posterior compression until fracture using a material testing machine, while surface strains were captured using a digital image correlation system. The effects of age, sex, bone mineral density, rib level and side, four global morphological factors (e.g. rib length), and seven rib cross-sectional morphological factors (e.g. cortical thickness, determined by μCT), on fracture load were statistically examined using Pearson correlation coefficients, Mann–Whitney U test as well as Kruskal–Wallis test with Dunn-Bonferroni post hoc correction. Fracture load showed significant dependencies (p < 0.05) from bone mineral density, age, antero-posterior rib length, cortical thickness, bone volume/tissue volume ratio, trabecular number, trabecular separation, and both cross-sectional area moments of inertia and was significantly higher at rib levels 7 and 8 compared to level 4 (p = 0.001/0.013), whereas side had no significant effect (p = 0.989). Cortical thickness exhibited the highest correlation with fracture load (r = 0.722), followed by the high correlation of fracture load with the area moment of inertia around the longitudinal rib cross-sectional axis (r = 0.687). High correlations with maximum external rib surface strain were detected for bone volume/tissue volume ratio (r = 0.631) and trabecular number (r = 0.648), which both also showed high correlations with the minimum internal rib surface strain (r =  − 0.644/ − 0.559). Together with rib level, the determinants cortical thickness, area moment of inertia around the longitudinal rib cross-sectional axis, as well as bone mineral density exhibited the largest effects on human rib fragility with regard to the fracture load. Sex, rib cage side, and global morphology, in contrast, did not affect rib fragility in this study. When checking elderly patients for rib fractures due to blunt chest trauma, patients with low bone mineral density and the mid-thoracic area should be carefully examined.